Análisis de la estimación de costos indirectos en obras de ingeniería civil en la zona de planificación 3 - Gavilanes Vargas, Erick Wladimir (2023)
The procedure used at the time of estimating indirect costs in the analysis of unit prices is practically empirical since it does not specify a detailed elaboration of the percentage used in the projects, ignoring the technical criteria on which the professionals are based for the placement of this value, and avoiding a thorough calculation method, in this way, the purpose of the research report is to analyze the calculation of indirect costs by prioritizing its most used components in the construction of sewerage works by bidding in planning zone 3, having in principle state of the art through documentary review and adding the collection of the public procurement system specifications, and employing a calculation method for the application of indirect cost. The research project used a quantitative and qualitative approach. Its design is non-experimental of descriptive type using a non-probabilistic sampling of construction projects. A Likert attitude survey was used as a data collection instrument to obtain the importance of the different components of the work that can affect the cost, its essential parameters, and the degree of conformity, where a multicriteria analysis was also performed to issue a comparison between the evaluation criteria, to obtain a hierarchy with priorities that show the preferences of the elements of indirect cost, and to verify the consistency of the evaluated criteria as a way to eliminate bias in its process, allowing to optimize the decision making when calculating indirect costs, having a consistency ratio (% CR= 8) being acceptable, and using Cronbach's Alpha, the reliability in the questions for the validation of the survey was evaluated. From the results obtained, it is revealed that the indirect cost is not calculated and that, on the contrary, the referential percentage is placed in the contracting process since when reviewing the files in the bidding documents, there is no memory of the calculation of the indirect cost, and this is ratified since the percentage most used by most of the contractors is 20%.